On the relationship between the non-photochemical quenching of the chlorophyll fluorescence and the Photosystem II light harvesting efficiency. A repetitive flash fluorescence induction study - Koblízek, M; Kaftan, D; Nedbal, L (Photosynthesis research, 2001)
Plants respond to excess light by a photoprotective reduction of the light harvesting efficiency. The notion that the non-photochemical quenching of chlorophyll fluorescence can be reliably used as an indicator of the photoprotection is put to a test here. The technique of the repetitive flash fluorescence induction is employed to measure in parallel the non-photochemical quenching of the maximum fluorescence and the functional cross-section (sigma(PS II)) which is a product of the photosystem II optical cross-section a(PS II) and of its photochemical yield Phi(PS II) (sigma (PS II) = a(PS II) Phi(PS II)). The quenching is measured for both, the maximum fluorescence found in a single-turnover flash (F(M) (ST)) and in a multiple turnover light pulse (F(M) (MT)). The experiment with the diatom Phaeodactylum tricornutum confirmed that, in line with the prevalent model, the PS II functional cross-section sigma (PS II) is reduced in high light and restored in the dark with kinetics and amplitude that are closely matching the changes of the F(M) (ST) and F(M) (MT) quenching. In contrast, a poor correlation between the light-induced changes in the PS II functional cross-section sigma (PS II) and the quenching of the multiple-turnover F(M) (MT) fluorescence was found in the green alga Scenedesmus quadricauda. The non-photochemical quenching in Scenedesmus quadricauda was further investigated using series of single-turnover flashes given with different frequencies. Several mechanisms that modulate the fluorescence emission in parallel to the Q(A) redox state and to the membrane energization were resolved and classified in relation to the light harvesting capacity of Photosystem II.